Superior Human Resources and Religious Tourism: Thriving Towards Sustainable Economic Independence - Widiati, Ari; Sari, Indah Purnama; Hidayat, Samsul (Relevance: Journal of Management and Business, 2024)
This research explores the relationship between the development of superior Human Resources (HR) and the development of religious tourism in the context of increasing sustainable economic independence. The main object of research is Muinul Islamic Boarding School, an Islamic educational institution that has great potential as a religious tourism destination in Indonesia. Through a qualitative approach with a field research method, this study identifies the key role of superior human resources in managing and optimizing the potential of religious tourism. To see the role of human resources in increasing sustainable economic independence and how religious tourism development strategies in increasing sustainable economic independence. The results showed that the development of religious tourism can contribute to the local economy, by creating jobs, learning media for entrepreneurial students, increasing income from tourism, and expanding economic opportunities for local communities. This research produces an overview of human resource development to support religious tourism to increase economic independence in Muinul Islam Islamic boarding school.